Primary School Network and Effective Implementation of the Univerasl Basic Educaton Programme in Owerri Education Zone of Imo State, Nigeria - Obasi, Kenneth; Madu, Onyewuchi M. (International Journal of Educational Management, 2021)
he study sought to determine the nature of primary school network for effective implementation of the Universal Basic Education programme in Owerri Education zone of Imo State, Nigeria. Two research questions guided the study. The study adopted the descriptive survey design. The population comprised all the 500 public primary schools with 14,923 basic six pupils in Owerri Education Zone of Imo State. Based on the nature of the study, the 500 public primary schools were used. This was to determine the school network. Out of 14,923 basic six pupils, a sample size of 5000 (34%) was drawn using stratified random sampling technique and they constituted the respondents of the study. The study used the Global Positioning System (GPS) instrument (proMark-3type) as the primary instrument. The instrument was complemented by a validated structured questionnaire titled: Primary School Network and the Implementation of the Universal of Basic Education Programme Questionnaire (PSNIUBEPQ) with a reliability index of 0.76. School location GPS coordinates, number of primary schools in each Local Government Area and the total area were used to determine the pattern of distribution of primary schools in the study area using Nearest Neighbor Analysis (NNA) statistics. Data collected with the questionnaire were analyzed using the simple percentage. The findings of the study revealed among others that the current primary school network in Owerri Education Zone of Imo State is of a clustered distribution pattern, this indicates that there is uneven distribution of primary schools in the area. It was recommended among others that the state government should come up with specific policies on school mapping and ensure their strict implementation to guarantee effective and efficient school network.